Engineering a nicking endonuclease N.AlwI by domain swapping - Xu, Yan (The National Academy of Sciences, 2001)
Changing enzymatic function through genetic engineering still presents a challenge to molecular biologists. Here we present an example in which changing the oligomerization state of an enzyme changes its function. Type IIs restriction endonucleases such as AlwI usually fold into two separate domains: a DNA-binding domain and a catalytic/dimerization domain. We have swapped the putative dimerization domain of AlwI with a nonfunctional dimerization domain from a nicking enzyme, N.BstNBI. The resulting chimeric enzyme, N.AlwI, no longer forms a dimer. Interestingly, the monomeric N.AlwI still recognizes the same sequence as AlwI but only cleaves the DNA strand containing the sequence 5′-GGATC-3′ (top strand). In contrast, the wild-type AlwI exists as a dimer in solution and cleaves two DNA strands; the top strand is cleaved by an enzyme binding to that sequence, and its complementary bottom strand is cleaved by the second enzyme dimerized with the first enzyme. N.AlwI is unable to form a dimer and therefore nicks DNA as a monomer. In addition, the engineered nicking enzyme is at least as active as the wild-type AlwI and is thus a useful enzyme. To our knowledge, this is the first report of creating a nicking enzyme by domain swapping.